Biomaterials for periodontal regeneration: A brief overview - Dhiraj B Dufare (Wolters Kluwer Medknow Publications, 2021)
The aim of periodontal regenerative therapy is to restore the original architecture and function of lost periodontal tissues as a result of trauma or following destructive periodontal diseases. This review includes the biological principles, efficacy, and effectiveness of different biomaterials and their limitation in periodontal regeneration. Various human clinical trials showed a successful periodontal regeneration with different biomaterials. The regenerative potential of biomaterials was assessed truly by human histological study. However, there were a limited number of human histological evidences to demonstrate the true regenerative potential of biomaterials; further human histological studies were required to establish strong evidences for application of biomaterials in the regeneration of periodontium.